(untitled) (KULT_online, 2015)
In his study, Christian Grüny explores music as ’Sinngeschehen’, as genuine production of sense. To do that he consistently avoids a comprehensive theoretical system. His ’philosophical constellations’ aim to carefully fit his own thinking to the movement of its object and thus allow to ’appear, what otherwise would pass unseen’.